2020
DOI: 10.3390/w12102745
|View full text |Cite
|
Sign up to set email alerts
|

Integrating C- and L-Band SAR Imagery for Detailed Flood Monitoring of Remote Vegetated Areas

Abstract: Flood detection and monitoring is increasingly important, especially on remote areas such as African tropical river basins, where ground investigations are difficult. We present an experiment aimed at integrating multi-temporal and multi-source data from the Sentinel-1 and ALOS 2 synthetic aperture radar (SAR) sensors, operating in C band, VV polarization, and L band, HH and HV polarizations, respectively. Information from the globally available CORINE land cover dataset, derived over Africa from the Proba V s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
2
18
0
2
Order By: Relevance
“…In general, the SARincF and SARwC FSs complemented by three or ten optical bands perform well and the optimal k lies around 10. This k value is in line with the findings of Refice et al [40], who initially opted for a higher number of clusters but obtained 12 distinct clusters after merging.…”
Section: K-means Cluster Classificationsupporting
confidence: 90%
See 3 more Smart Citations
“…In general, the SARincF and SARwC FSs complemented by three or ten optical bands perform well and the optimal k lies around 10. This k value is in line with the findings of Refice et al [40], who initially opted for a higher number of clusters but obtained 12 distinct clusters after merging.…”
Section: K-means Cluster Classificationsupporting
confidence: 90%
“…They furthermore observed an increasing backscatter difference with decreasing incidence angles, in accordance with previous research, except for very sharp incidence angles (23.5 • ) at which the detectability dropped sharply [37][38][39]. Long et al [14] successfully mapped flooded marshland using a threshold of 7.7 dB on a C-HH difference image, while Tsyganskaya et al [19] observed a backscatter increase of about 2 dB for an example FV segment with C-VV and Refice et al [40] reported a backscatter increase of almost 5 dB in C-VV for a cluster comprising mainly flooded herbaceous vegetation. An overview of relevant findings for C-as well as X-and L-band is given by Martinis and Rieke [41].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, several unknowns (e.g., structure and geometry for vegetation, or height and orientation of buildings for urban areas) influence the radar response from these targets [8]. Consequently, although new insights were provided on detecting inundations in agricultural areas [9][10][11][12][13] and urban settlements [8,[14][15][16][17], this task is still very challenging. Not only missed detections (i.e., omission errors), but also commission errors may occur when mapping surface water.…”
Section: Introductionmentioning
confidence: 99%